EMPLOYEES’ WELL-BEING AS A MEDIATOR OF THE RELATIONSHIP BETWEEN HR PRACTICES AND JOB MOTIVATION IN MANUFACTURING INDUSTRY - Nurfarahain Binti Jalil; Ishak Bin Haji Abd Rahman; Azmi bin Aziz (International Journal of Accounting, Finance and Business, 2021)
This study was conducted to assess the relationship between HR practices and job motivation mediating employees’ well-being. Recent studies from the perspective of social exchange which focus on the HR practices and job motivation have a significant impact towards positive employees’ well-being. The nature of this relationship is emphasized in human resource management models. The evidence is used as a foundation to develop a conceptual schema for this study. The data was collected using survey on 136 usable questionnaires from employees who worked in manufacturing industry. The findings from the Statistical Package for Social Science (SPSS) using a stepwise regression analysis revealed that this study contributes to 51% variance on the proposed model. This result confirms that employees’ wellbeing does act as a full mediating variable in the HRM models of the organizational sector sample. In addition, the implications of this study to social exchange theory and practice, methodological and conceptual limitations and directions for future research are discussed.